Ear photosynthesis in C3 cereals and its contribution to grain yield: Methodologies, controversies, and perspectives - Tambussi, Eduardo Alberto (2021)
In C3 cereals such as wheat and barley, grain filling was traditionally explained as being sustained by assimilates from concurrent leaf photosynthesis and remobilization from the stem. In recent decades, a role for ear photosynthesis as a contributor to grain filling has emerged. This review analyzes several aspects of this topic: (i) methodological approaches for estimation of ear photosynthetic contribution to grain filling; (ii) the existence of genetic variability in the contribution of the ear, and evidence of genetic gains in the past; (iii) the controversy of the existence of C4 metabolism in the ear; (iv) the response of ear photosynthesis to water deficit; and (v) morphological and physiological traits possibly related to ear temperature and thermal balance of the ear. The main conclusions are: (i) there are a number of methodologies to quantify ear photosynthetic activity (e.g. gas exchange and chlorophyll fluorescence) and the contribution of the ear to grain filling (individual ear shading, ear emergence in shaded canopies, and isotope composition); (ii) the contribution of ear photosynthesis seems to have increased in modern wheat germplasm; (iii) the contribution of the ear to grain filling increases under resource-limitation (water deficit, defoliation, or pathogen infection); (iv) there is genetic variability in the contribution of the ear in wheat, opening up the possibility to use this trait to ameliorate grain yield; (v) current evidence supports the existence of C3 metabolism rather than C4 metabolism; (vi) the ear is a 'dehydration avoider organ' under drought; and (vii) thermal balance in the ear is a relevant issue to explore, and more research is needed to clarify the underlying morphological and physiological traits.